2021
DOI: 10.1055/s-0041-1726128
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of the Multilayered Skull Base Reconstruction Using In Situ Bone Flap in Endoscopic Endonasal Approach for Craniopharyngioma

Abstract: Objective The aim of the study is to summarize and analyze the efficacy of the multilayered skull base reconstruction using in situ bone flap in endoscopic endonasal approach (EEA) for craniopharyngiomas. Methods A retrospective review of 65 patients who underwent resection of their histopathology confirmed craniopharyngiomas performed at a single institution. Based on the team's understanding and mastery of skull base reconstruction techniques, patients were divided into two groups according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…(31) Previous studies have demonstrated the effectiveness of applying ISBF for skull base reconstruction in surgery. (31,32) However, there are no studies exploring the role of ISBF in skull base reconstruction in EEA surgery for IPAs. Our investigation revealed that the ISBF technique was also effective in reducing the incidence of postoperative CSF leak in IPA patients.…”
Section: Discussionmentioning
confidence: 99%
“…(31) Previous studies have demonstrated the effectiveness of applying ISBF for skull base reconstruction in surgery. (31,32) However, there are no studies exploring the role of ISBF in skull base reconstruction in EEA surgery for IPAs. Our investigation revealed that the ISBF technique was also effective in reducing the incidence of postoperative CSF leak in IPA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Through the study of this group, we found that the " in situ bone flap" reconstruction technique provides a rigid reconstruction of the saddle bottom, and the results are safe and effective. We conclude that the "in situ bone flap" technique has the following advantages: (1) The application of this " in situ bone flap" technology, the bone flap comes from the operative area, does not need to remove the surgical area, reduces the process of entering and leaving the narrow space of the nasal cavity, reduces the damage of the nasal mucosa, and reduces the operation time[ 34 , 35 ]; (2) The bone flap is the bone of the surgical site, and the size and shape of the bone flap match the bone window of the skull base, which is a kind of anatomical reduction operation and fully meets the requirements of skull base reconstruction[ 36 - 39 ]; (3) After rigid bone reconstruction, the anatomical layers are clearly defined, and there are no disadvantages such as rejection and foreign body, which greatly reduces adhesion and postoperative scar formation in the operative area , and facilitates the expedient healing and re-operation of tumor recurrence[ 30 , 40 , 41 ]; and (4) Through rigid bone reconstruction, the direct impact of cerebrospinal fluid on mucosal flap is slowed down, the reconstruction is enhanced, and the medium is provided for the growth and adhesion of mucosal flap, which has a positive effect on the fixation and survival of mucosal flap after surgery[ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the application of ISBF can significantly reduce the rate of postoperative CSF leakage following EEA ( 30 , 32 , 33 ); however, few of them have focused on pituitary adenoma. Pituitary adenomas are the most common type of pituitary disorder.…”
Section: Discussionmentioning
confidence: 99%